HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN EFIKASI DIRI PADA SISWA KELAS X AKUNTANSI DI SMK BINA PANGUDI LUHUR JAKARTA - ANITA SARI; ATI SUMIATI (Fakultas Ekonomi Universitas Negeri Jakarta, 2016)
ABSTRACT This research was aimed to obtain valid and reliable data about Relationship between Social Support with Self Efficacy Grade X Accounting in Vocational High School Bina Pangudi Luhur Jakarta. This research was conducted by survey method and correlational approach. Sampling technique used proportional random sampling. Affordable population in this research were Grade X Accounting students with totaling 63 students. Total of samples used were 55 students. The results showed that: there is a positive relationship between social support with self efficacy Grade X Accounting in Vocational High School Bina Pangudi Luhur Jakarta. Thus if the social support increases, the self efficacy will also increase. Key words: social support, self efficacy.